English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

I do an online program and i am a senior in high school. With this program I have no teacher and I get no practice. I am doing functions but have no clue how to do some. How do you do these?
1. f(x) = x2 + 7x
Find f(-3)

2. f(x) = -3x + 9
g(x) = 8x + 7
Find f(x) + g(x)

3. f(x) = -3x + 9
g(x) = 8x + 7
Find f(g(x))

4. f(x) = 4xSquared
h(x) = -7x - 5
Find h(f(3))

5. h(x) = 2x3 - 5x2
Find h(3)

6. h(x) = 2x3 - 5x2
Find h(-5)

7.f(x) = 15 - 6x
g(x) = 3 x
5
Find g(f(x))

8. f(x) = x3 - x2 - 3x + 5
Find f(4)

THANK YOU FOR ANY HELP THAT YOU CAN GIVE ME. I GREATLY APPRECIATE IT.

2007-11-18 16:17:10 · 6 answers · asked by Anonymous in Science & Mathematics Mathematics

6 answers

I'll assume that "f(x) = x2 + 7x" was written so that the 2 was smaller and set above the line as a superscript, near the upper-right corner of the letter x (something I can't do here). That notation means "x to the power 2," or x times x.

In that case, the function is "f(x) = x*x + 7*x",
so f(-3) = -3 * -3 + 7 * -3 = 9 - 21 = -12

FYI:
"x to the power 3" would be x*x*x,
"x to the power 4" would be x*x*x*x,
and so on.

When the problem is f(g(x)), break it into pieces:
y = g(x)
result = f(y)

2007-11-18 16:34:33 · answer #1 · answered by Tom V 6 · 0 0

1. f(x) = x2 + 7x
f(-3)=
-3*2 + 7*-3=
-6+-21=
-27

2. f(x) = -3x + 9
g(x) = 8x + 7
f(x) + g(x)=
-3x + 9 +8x + 7=
5x+16

3. f(x) = -3x + 9
g(x) = 8x + 7
f(g(x))=
f(8x + 7)=
-3*(8x + 7) + 9=
-24x-21+9=
-24x-12

4. f(x) = 4xSquared
h(x) = -7x - 5
h(f(3))=
h(4*3Squared)=
h(4*9)=
h(36)=
-7*36 - 5=
-252 - 5=
-257

5. h(x) = 2x3 - 5x2
I'm going to assume that means 2x^3-5x^2. (That means 2x Cubed-5x Squared.) Therefore
h(3)=
2*3^3-5*3^2=
2*27-5*9=
54-45=
9

6. h(x) = 2x3 - 5x2
Same assumption here.
h(-5)=
2*(-5)^3 - 5*(-5)^2=
2*-125-5*25=
-250-50=
-300

7.f(x) = 15 - 6x
g(x) = 3 x
5
Find g(f(x))
I don't know why you have a random number 5 on the third line, so I'm going to skip this one.

8. f(x) = x3 - x2 - 3x + 5
I'm going to assume that means x^3 - x^2 - 3x + 5. Therefore
f(4)=
4^3 - 4^2 - 3*4 + 5=
64-16-12+5=
41

2007-11-18 16:32:50 · answer #2 · answered by Anonymous · 0 0

Ok so this is how you do function....
First you got to know that f(x) is the same as y

1. If f(-3) then f(x)= x2 + 7x Plug in
f(-3)=(-3)2 + 7(-3)
f(-3)= -6 + (-21)
f(-3)= -27

2007-11-18 16:27:41 · answer #3 · answered by The one 1 · 0 0

1. f(x) = x2 + 7x
Find f(-3)

let f(-3) = (-3)^2 + 7(-3)

= 9 - 21

therefore, f(-3) = -12
------------------------------------------
2. f(x) = -3x + 9
g(x) = 8x + 7
Find f(x) + g(x)

let -3x + 9 + 8x +7

5x + 16

therefore, f(x) + g(x) = 5x + 16
------------------------------------------------

3. f(x) = -3x + 9
g(x) = 8x + 7
Find f(g(x))

let, f(8x + 7) = -3(8x + 7) + 9

= -24x - 21 + 9

= -24x - 12

therefore, f(g(x)) = 24x - 12
---------------------------------------------------

4. f(x) = 4xSquared
h(x) = -7x - 5
Find h(f(3))

solve for f(3) first,
f(3) = 4[(3)^2]

= 4(9)

= 36

then solve for h(f(3))..
given that f(3) = 36

h(36) = -7x - 5

= -7(36) - 5

= -252 - 5

= -257

therefore,h(f(3)) = -257

5. h(x) = 2x3 - 5x2
Find h(3)

h(3) = 2[(3)^3] - 5[(3)^2]

= 2(27)- 5(9)

= 54 - 45

= 9

therefore, h(3) = 9

2007-11-18 17:11:24 · answer #4 · answered by Nonoi_Orange 2 · 0 0

1. Substitute -3 for x in the function. A similar deal for 5, 6, and 8.
2. Add the two functions together.
3. where you see x in f(x), substitute g(x). Same for 7.
4. Substitute 3 for x in f(x) and find numerical result. Substitute that in for x in h(x).

2007-11-18 16:29:51 · answer #5 · answered by cattbarf 7 · 0 0

You plug the number into the equation...

2007-11-18 16:20:47 · answer #6 · answered by topher098321 2 · 0 0

fedest.com, questions and answers